Calibrations of thermo-hydro-mechanical coupling parameters for heating and water-cooling treated granite. (May 2021) - Yang, Fujian; Wang, Guiling; Hu, Dawei; Liu, Yanguang; Zhou, Hui; Tan, Xianfeng
Abstract: Knowledge of thermo-hydro-mechanical (THM) coupling process is important for rock hydrofracturing of enhanced geothermal systems (EGS). The THM coupling parameters (e.g. thermal conductivity, water permeability and Biot's coefficient, etc) of granite undergoing treatment with heating and water cooling (HWC) were measured using laboratory tests. A large number of cracks inside the granite are caused by the uncoordinated deformation of minerals and the tensile stress induced by the treatment of HWC were clearly observed by scanning electron microscope (SEM), resulting in degradations of physico-mechanical behavior and capacity of heat transmission, and increases of effective stress and connectivity of transport path. Compared with the treatments of heating and natural cooling or heating in real-time in previous studies, the temperature threshold of THM coupling parameters are advanced for HWC treated granite, especially for thermal conductivity, water permeability, Biot's coefficient and brittle–plastic transition. Prediction models for THM coupling parameters are established based on the correlation analysis. The predictions are in good agreement with the experimental observations. The results are likely to provide an outlet for understanding the characteristics of dry hot rock undergoing hydraulic fracturing or thermal stimulation, especially for the variations and predictions in THM coupling parameters. Highlights: Treatment of heating and water cooling could exacerbate thermal cracking. Reduction of thermal conductivity, increases of effective stress and transport path. Temperature threshold of thermo-hydro-mechanical coupling parameters are advanced. Establishing prediction model for thermo-hydro-mechanical coupling parameters.